Effectiveness of nurse‐led discharge service on adult surgical inpatients: A meta‐analysis of randomized controlled trials - Huina Mao; Yarui Xie; Ying Shen; Mei Wang; Yingxia Luo (Wiley, 2022)
Abstract Aim To determine the effectiveness of nurse‐led discharge service for adult surgical inpatients. Design The report of this review was conducted by the preferred reporting items for systematic reviews and meta‐analyses (PRISMA) statement checklist. Methods The PubMed, Web of Science, ScienceDirect, Cochrane Library (CENTRAL), MEDLINE and Embase as well as four Chinese databases including CNKI, Wanfang database, VIP database and CBM were searched for randomized controlled trials. Two reviewers independently extracted data and assessed risk of bias. And meta‐analyses were conducted for the eligible studies by Review manager 5.4.1. Results A total of 1,649 participants were enrolled in 12 randomized controlled trials. The result of readmission rate and emergency visit of intervention group were lower than those of the control group; activities of daily living and quality of life in the intervention group were higher than that of the control group. There was no statistical difference in the length of stay between the two groups.